Temporal changes and predictors of perioperative blood transfusion in elective spine surgery: a retrospective analysis of a large surgical database. (April 2023) - Terada, Rui; Stewart, Kenneth; Hansen, Sandra; Shettar, Shashank S.; Butt, Amir; Vallurupalli, Santaram; Martin, Michael; Tanaka, Kenichi
Abstract: Background: Allogeneic blood transfusion used to be common in spine surgery. Patient blood management has been widely adopted, and it is important to reassess transfusion predictors in contemporary practice. Methods: A retrospective study of inpatient spine surgery was performed using National Surgical Quality Improvement Program (NSQIP) data from 2011 to 2019. The primary outcome was perioperative transfusion within 72 h of surgery. Multivariable logistic regression and recursive partitioning were used to assess up to 15 variables including patient and surgical data, surgical specialty (orthopaedic surgery vs neurosurgery), and year of surgery. Results: The study population included 251 971 US surgical patients; 6.9% of these patients received perioperative blood transfusion. Perioperative transfusions declined over time with the steepest decline from 2011 to 2015. The greatest reduction was seen among orthopaedic cases where the transfusion rate declined from 16.0% to 8.7% between 2011 and 2015. Eight variables were predictive factors in a reduced model: operative time, preoperative haemoglobin, vertebral level, number of vertebral levels, older age, surgeon specialty, arthrodesis, and year of surgery (area under the curve [AUC]=0.880; 95% confidence interval [CI], 0.878–0.883). Overall, longer operative time (>144 min) and greater numbers of vertebral levels had greater associations with transfusion than surgical specialty after adjustments. Prevalence of anaemia (15%) has not substantially declined. Conclusions: Perioperative blood transfusion rate in spine surgery has declined over the past decade. The extent and duration of surgery and preoperative haemoglobin level remain important factors associated with increased odds for perioperative blood transfusion.